A Network Mobility route optimization scheme for consumer multicast traffic in aeronautical communication - Chao Zhi; JinChun Gao; Gang Xie; Haiyang Liu; Yuan'an Liu (2016 2nd IEEE International Conference on Computer and Communications (ICCC), 2016)
Network Mobility (NEMO), an extension of Mobile IPv6, has been drawing attention of researchers. NEMO can provide Internet connectivity for a group of nodes, so it is suitable for Aeronautical Passenger Communication. As the core technology of Internet broadcast system, multicasting is also used in NEMO. However, when NEMO is nested, triangle routing problem, which is caused by large distance between the mobile nodes(MN) and home agents(HA), will increase the end-to-end latency and reduce the utilization of communication bandwidth. In this paper, we propose a new route optimization scheme to solve the triangle routing problem. The scheme utilizes local-mobility anchor(LMA) management domain, so the packets from or to NEMO onboard have no need to be forwarded by HAs, and the route is optimized. The analysis and simulation results indicate that the proposed scheme reduces the end-to-end communication delay.